2008
DOI: 10.1111/j.1365-2818.2008.02133.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between light and electron microscopy in canine and feline renal pathology: a preliminary study

Abstract: Summary The aim of this study is to compare the accuracy and clinical use of light and transmission electron microscopy in detecting the early stages of renal pathologies in domestic animals. We examined 30 samples of renal tissue from cats and dogs referred to the Veterinary Hospital of the Department of Animal Pathology for different systemic diseases. The progressions of the kidney pathologies were classified using the scheme system proposed by the International Renal Interest Society. All samples were subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Previous studies have indicated that the pathological mechanisms of the incidence and progression of CKD differ between dogs and cats. Previous investigations on the histopathological differences between canine and feline kidney disease show that tissue damage appears to be prominent in the glomerulus in dogs and in the tubulointerstitium in cats [16,22]. The results of our recent study demonstrate these species-specific histopathological features [29], and we suggest that the mechanisms for development of myofibroblasts, which play critical roles in renal fibrosis, differ between canine and feline CKD.…”
supporting
confidence: 63%
“…Previous studies have indicated that the pathological mechanisms of the incidence and progression of CKD differ between dogs and cats. Previous investigations on the histopathological differences between canine and feline kidney disease show that tissue damage appears to be prominent in the glomerulus in dogs and in the tubulointerstitium in cats [16,22]. The results of our recent study demonstrate these species-specific histopathological features [29], and we suggest that the mechanisms for development of myofibroblasts, which play critical roles in renal fibrosis, differ between canine and feline CKD.…”
supporting
confidence: 63%
“…Ultrastructural evaluation provides useful diagnostic information in nearly 50% of nontransplant human renal biopsy specimens, allowing assessment of the glomerular basement membrane (GBM) and podocyte foot processes, as well as confirmation of the presence or absence of immune complex deposits. A previous preliminary study of TEM in canine and feline renal pathology concluded that TEM also is necessary to complement histological examinations in dogs . Indeed, many glomerular diseases are at least partially defined by distinctive changes in cells, extracellular matrix, or both that can only be detected by TEM …”
mentioning
confidence: 99%
“…A previous preliminary study of TEM in canine and feline renal pathology concluded that TEM also is necessary to complement histological examinations in dogs. 11 Indeed, many glomerular diseases are at least partially defined by distinctive changes in cells, extracellular matrix, or both that can only be detected by TEM. 12 There are no large-scale studies defining the prevalence of ICGN in dogs with clinical evidence of glomerular disease for which renal specimens were evaluated by LM, IF, and TEM in all cases.…”
mentioning
confidence: 99%